Pengaruh Economic Value Added (EVA), Return On Equity (ROE) dan Dividend Payout Ratio (DPR) Terhadap Harga Saham Perusahaan Manufaktur di BEI - Wijaya, I Gede Oka; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen, 2017)
The purpose of this research is to determine the effect of economic value added, return on equity and dividend payout ratio to the stock price in manufacture sector in BEI. Sampling determination technique in this research use saturated sampling, which is sampling determination technique when all populations used as sample and the final sample is 15 manufacture companies listed in Indonesia Stock Exchange on 2011-2013. Data collection methods used in this study is a non-participant observation. This study uses multiple linear regression analysis with the help of SPSS 22 for windows. The result of the research shows that only return on equity variable have positive and significant effect to the stock price, meanwhile economic value added and dividend payout ratio have no effect to the stock price on manufacture companies in Indonesia Stock Exchange.